Factors Affecting Purchase Intention in Indonesian Online Retailers (Journal of Business and Management, 2021)
Online fashion retailers have an influential impact on the e-commerce portals as well as on fashion conscious consumers which have been very significant and shown tremendous results in the fashion retail industry. This research is going to investigate about how trust and website quality have a connection with the intention of online purchasing. Data was collected using a survey, involving 390 individuals. Multiple regression analysis was conducted to ascertain how trust and website quality influence customers' buying intentions when it comes to fashion e- commerce sites. According to the findings, trust and website quality were identified as the catalysts for a new wave of digital revolutions originating from e-commerce players such as Zalora and Pomelo to target generation groups in Indonesia, as these online retailers have surpassed the country's major economies. As a recommendation, potential studies in on fast fashion e-commerce should focus on the impact of moderating variables such as previous Internet and online shopping experience on purchasing intention.Keywords: online fashion, e-commerce, purchase intention, trust, website quality